Social Capital Integration Model Training in Physical Education and Sports - Syarifatunnisa Syarifatunnisa; Anira Anira; Amung Ma'mun; Suherman Slamet; Risma Risma (Universitas Pendidikan Indonesia Kampus Purwakarta, 2023)
This training aims to disseminate information about the meaning of student involvement in physical education activities that can be used as development instruments, especially for developing social capital, which is a provision in navigating life throughout their lives. Increasing teachers' understanding of the learning process in schools makes physical education activities a social movement with more advantages for the government and society to realize the community's social life as expected. This training was held at the Auditorium of the Graduate School, Universitas Pendidikan Indonesia. The result of this training is that the participants are able to design the Social Capital Integration Model program in the Guidance and Development of Physical Education and Sports in the learning process. This training is an initial step to introduce participants to how to create a program to achieve the learning objectives.